Perfil Lipídico y su relación con la presencia de enfermedades Cardiovasculares en los Habitantes del Barrio San Vicente del Río. - Granillo Espinoza, Tanya Maritza (2013)
The incident of cardiovascular diseases, generally it increases in relation with the concentration of lipids in the organism. According to the World Health Organization, the cardiovascular diseases are the principal reason of death in the whole world. In the inhabitants of San Vicente of the Rio of the canton Avocadoes, persons exist with hypertension, overweight and cases of genetic origin, according to the clinical history of the patients who come to the Social Rural Insurance who in the main do not receive medical control. Reason for which it proposed to quantify the profile lipid of the 20-year-old major persons, to know the reasons of increase of the profile lipid, and the factors of risk that can be modified to diminish the risk of cardiovascular diseases. In the investigation there was applied a descriptive study of transverse court, procedures were implemented for the compilation of information and 53 patients were selected by means of the application of a survey that they constituted the sample, later there was realized the capture and analysis of the blood samples by means of the enzymatical method - colorimetric, the obtained results were tabulated and analyzed. In conclusion the permanent quantification of the levels of lipids and his medical valuation, accompanied of balanced supply and the physical exercise, they reduce the exhibition to the cardiovascular risks, improving this way the quality of life of the persons. Keywords: Lipid profile, Cardiovascular Diseases, Risk Factors